Vulneración del principio de mínima intervención por inaplicación de MASC en el delito de estafa. - Troya, Edgar A. (2022)
The content study of the scientific article takes into consideration as a general objective: Analyze the violation of the principle of minimum criminal intervention by preventing the applicability of alternative methods to conflict resolution in the crime of fraud in the Comprehensive Organic Criminal Code. Then, within the Constitution of the Republic of Ecuador (2008), an important advance is established in terms of the application of alternative methods of conflict resolution within disputes and processes in Ecuador, so that, within the matter that corresponds in the Organic Comprehensive Criminal Code, if it links the application of said methods in the crimes that stipulate them in a detailed manner and that comply with the specific conditions. In the daily practice of law, it has been clearly shown that in most cases of fraud the procedural parties want to reach an agreement to avoid long and cumbersome processes, so this research has the purpose of studying the doctrinal reasons, normative and of the people who come across the practice of law on a daily basis, which is why it has been necessary to conduct interviews with the officials in charge of making justice possible. From which it follows that the principle of legality must be applied, however, there could be a reform within which the parties are empowered to submit to alternative methods of conflict resolution.